Persepsi Dosen Pembelajaran Bahasa Inggris UIN Alauddin Makassar terhadap Pengembangan Profesi Dosen - Indy Trini Humaerah; Haryanto Atmowardoyo; Muhammad Asfah Rahman (Universitas Islam Negeri Alauddin Makassar, 2023)
Professional Development has played an essential role in ELT in Indonesia, where English is considered a foreign language. Regarding this, the researcher is aimed to find out the perceptions of EFL lecturers about the types of Professional Development activities most influence the lecturers' classroom activities, and the impact of Professional Development on lecturers' teaching practices. This research used a descriptive qualitative method involving 20 EFL lecturers in the English Education Department of Tarbiyah and Teaching Training Faculty, UIN Alauddin Makassar. The data revealed that the Professional Development activities have high-positive impact towards their teaching practices. Based on the finding, it can be concluded that EFL lecturers have a good perspective on Professional Development activities and help them improve the level of the criteria of a competent teacher.